Investigation of the efficiency of the application of modified vegetable oil lecithins for the creation of encapsulated forms of micronutrients in the form of nanoemulsions - E. V. Lisovaya; E. P. Viktorova; A. V. Sverdlichenko; M. R. Zhane (Новые технологии)
Micro- and nanoemulsions are promising systems for encapsulating micronutrients for food enrichment. For the formation of stable nanoemulsions, it is advisable to use natural emulsifiers – modified lecithins of vegetable oils. The aim of the research is to study the effectiveness of the use of modified lecithins of vegetable oils to create encapsulated forms of micronutrients in the form of nanoemulsions. Emulsions have been obtained using the method of ultrasonic exposure with the use of fat-free vegetable lecithins and their alcohol-soluble fractions as emulsifiers. It has been found that the particle size of emulsions formed by fat-free lecithins is significantly higher compared to the emulsions formed by their alcohol-soluble fractions. It has been revealed that emulsions formed by alcohol-soluble fractions of lecithins are more resistant to delamination. It is shown that alcohol-soluble fractions of vegetable lecithins with a PH content from 75.0 to 76.0% have the highest emulsifying properties, which makes it possible to obtain physically stable nanoemulsions with an average particle size of the dispersed phase less than 100 nm. Thus, modified lecithins of vegetable oils, namely, alcohol-soluble fractions of lecithins are highly effective encapsulating agents for creating encapsulated forms of micronutrients in the form of nanoemulsions.